2022
DOI: 10.1186/s12998-022-00462-0
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported attitudes, skills and use of evidence-based practice among Swiss chiropractors: a national survey

Abstract: Study Objectives The high burden of disease associated with musculoskeletal disorders severely impacts patients’ well-being. As primary care providers, Swiss chiropractors ought to contribute towards identifying and using effective treatment strategies. An established approach is the full integration of evidence-based practice (EBP). This study aimed to investigate the attitudes, skills and use of EBP among Swiss chiropractors, as well as investigating potential facilitators and barriers for it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In addition, our sample of chiropractic students also showed ceiling effects in 5 of 6 attitude subscale questions and 7 of 9 future use subscale questions which may demonstrate high affinity towards EBP constructs even prior to the journal club. However, a published article on self-reported attitudes, skills and use of evidence-based practice among Swiss chiropractors showed that 52% of respondents did not understand the full definition of EBP, which recognises that a patient’s preference also has to be taken into account for EBP [ 30 ]. Other national surveys of postgraduate chiropractors from the Canada, Sweden and the U.S., showed low to moderate subscores in EBP knowledge and use [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our sample of chiropractic students also showed ceiling effects in 5 of 6 attitude subscale questions and 7 of 9 future use subscale questions which may demonstrate high affinity towards EBP constructs even prior to the journal club. However, a published article on self-reported attitudes, skills and use of evidence-based practice among Swiss chiropractors showed that 52% of respondents did not understand the full definition of EBP, which recognises that a patient’s preference also has to be taken into account for EBP [ 30 ]. Other national surveys of postgraduate chiropractors from the Canada, Sweden and the U.S., showed low to moderate subscores in EBP knowledge and use [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our sample of chiropractic students also showed ceiling effects in 5 of 6 attitude subscale questions and 7 of 9 future use subscale questions which may demonstrate high a nity towards EBP constructs even prior to the journal club. However, a published article on self-reported attitudes, skills and use of evidence-based practice among Swiss chiropractors showed that 52% of respondents did not understand the full de nition of EBP, which recognises that a patient's preference also has to be taken into account for EBP [30]. Other national surveys of postgraduate chiropractors from the Canada, Sweden and the U.S., showed low to moderate subscores in EBP knowledge and use [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies with general practitioners and chiropractors show that among others, time constraints are the main barriers to following evidence‐based guidelines (e.g. ordering spine imaging is less time intensive than explaining why it is not needed) (Albisser et al., 2022; Pike et al., 2022). Second, even full adherence to guidelines would likely result in unsatisfactory treatment for many patients with NSLBP.…”
Section: The Current ‘Gold Standard’ To Treat Patients With Nslbpmentioning
confidence: 99%